Estimation of three-dimensional structure on peripheral fluctuation using fast camera images and magnetic field calculation in Heliotron J. (August 2019) - Nishino, N.; Mizuuchi, T.; Okada, H.; Ohshima, S.; Kobayashi, S.; Minami, T.; Kado, S.; Yamamoto, S.; Nagasaki, K.; Kawazome, H.
Highlights: Peripheral fluctuation such as filament in the fast camera image in Heliotron J should be along the magnetic field line, and this was compared with the projection image of the magnetic field line in peripheral region. The examined discharge was low toroidal current, negligible Shafranov shift; the magnetic field line of vacuum magnetic surface was used. As a result, the position of the filament could be specified, and the apparent poloidal speed of the filament was calculated. This method should be very useful to analyze behavior of the filament in Heliotron J plasma taken with in the past. Abstract: In Heliotron J, peripheral plasma fluctuation and/or turbulence have been measured by using a fast camera for over 10 years. Many image data are provided as two-dimensional information of time series by a fast camera, and they represent the spatial shape of fluctuation and its complex behavior. From experience in Heliotron J experiment, most of the peripheral fluctuations have elongated spatial structure along magnetic field lines. Because the movement of electrons and ions along the field lines is much faster than their vertical motion, this is natural; the filamentary structure along the field lines should be formed as a fundamental of many types of fluctuations in Heliotron J. In the image of the fast camera, if the fluctuation having a filamentous structure along the magnetic field line is observed as a brighter region than its surrounding plasma, the image of this fluctuation should coincide with the projection image of the magnetic field line passing through the position of this fluctuation. That is, by comparing the projected image of magnetic field lines and the image of fluctuation images, three-dimensional information on peripheral plasma fluctuation can be obtained. Therefore, with the help of geometry of magnetic field lines, to extract three dimensional information about the fluctuation in Heliotron J from the two-dimensional image was tried. As a result, in the analysed range, the filament was along the magnetic field line; it appeared to occur from the O-point in the field of view, and disappear at the X-point. Apparent speed in the poloidal cross-section was approximately 500 m/s. In the future, if this analysis method is applied, more detailed data on fluctuation will be obtained in Heliotron J.